2017
DOI: 10.1002/jbmr.2915
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genetic Correlations for Bone Microarchitecture: The Framingham Study Families

Abstract: High-resolution peripheral quantitative computed tomography (HR-pQCT) measures bone microarchitecture and volumetric bone mineral density (vBMD), important risk factors for osteoporotic fractures. We estimated the heritability (h2) of bone microstructure indices and vBMD, measured by HR-pQCT, and genetic correlations (ρG) among them and between them and regional aBMD measured by dual-energy X-ray absorptiometry (DXA), in adult relatives from the Framingham Heart Study. Cortical (Ct) and trabecular (Tb) traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
4
25
0
1
Order By: Relevance
“…Thus, our finding of substantial heritabilities of height‐ and other covariate‐adjusted failure load—from 47% to 52% (radius) and 50% (tibia)—is significant. This h 2 estimate is comparable with the heritability for covariate‐adjusted ultradistal radius aBMD (41.7%) and femoral neck aBMD (54.3%) in the Framingham sample.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Thus, our finding of substantial heritabilities of height‐ and other covariate‐adjusted failure load—from 47% to 52% (radius) and 50% (tibia)—is significant. This h 2 estimate is comparable with the heritability for covariate‐adjusted ultradistal radius aBMD (41.7%) and femoral neck aBMD (54.3%) in the Framingham sample.…”
Section: Discussionsupporting
confidence: 63%
“…Scans were qualitatively graded according to a 5‐point progressive movement scale (1 = perfect, 5 = severe motion artifact). For the micro‐finite element analysis, scans with extreme movement (a movement grade > 3) were excluded . Data capture was supported by REDCap .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study examining HR‐pQCT microstructure of monozygotic and dizygotic middle‐aged white female twin pairs indicated that genetic factors accounted for 72% to 81% of the variance of microstructure, suggesting genetics plays a stronger role than environmental factors in bone microarchitecture . Furthermore, data from the Framingham Offspring cohort found high heritability of HR‐pQCT traits ranging from 19.3% for radial trabecular number to 98.3% for tibial cortical cross‐sectional area . Future studies are needed to assess the genes associated with these microstructural characteristics, as differences in allele frequencies between the white and Chinese populations in genes associated with microstructure may contribute to the microstructural skeletal advantages observed here among Asian individuals.…”
Section: Discussionmentioning
confidence: 99%